Pattern of Sexually Transmitted Infections at Kohalpur Teaching Hospital - Pandey, Sumit; Sharma, Nirmala; Pokhrel, Nitesh; Joshi, Shambhu (Journal of Nepalgunj Medical College, 2017)
Background: WHO estimated that approximately 448 million new cases of four main curable sexually transmitted infections (STIs), viz., gonorrhoea, syphilis, chlamydial infection, and trichomoniasis occur every year, nearly 80% of which in developing countries. STIs has proven role in facilitation of HIV infection and also increases susceptibility to other STIs. Most of the STIs, both ulcerative and non-ulcerative, are prevalent in Nepal and constitute one of the major health problem. Their epidemiological and clinical picture is being modified in the context of ongoing HIV/AIDS epidemic, especially during the last decade. Objectives: This study was undertaken to find out the pattern of sexually transmitted infections in Nepalgunj Medical College Teaching Hospital, Kohalpur. Method and material: This is a hospital - based descriptive study conducted in the Department of Dermatology, Venereology and Leprology of Nepalgunj Medical College Teaching Hospital, Kohalpur between August 2013 to July 2014. A total of 52 patients were included in the study and verbal consent was taken. History and clinical examinations were performed and the data were recorded and analyzed. Results: Total of 52 patients were diagnosed with Sexually Transmitted Infections, out of which 75% were male and 25% were female. The most common diagnosis was gonorrhea (34.6%) followed by condyloma accuminata (32.7%), latent syphilis (15.4%) non-gonococcal urethritis(9.6%), vaginal discharge syndrome (5.8%)and HIV (1%). Age group 21 to 30 years were the maximum sufferers. Conclusion: Gonorrhoea still comprises a major bulk of STI in Nepalgunj Medical College Hospital, Kohalpur. Majority of the patients suffering from sexually transmitted infections were in the age group 21-30 years. A trend of sexual exposure during adolescence with multiple partners and inconsistent use of condoms was observed as a common factor in its promotion despite efforts from various sectors. Journal of Nepalgunj Medical College Vol.13(1) 2015: 25-27